Development of products and services in small enterprises: proposition of an artifact to discuss creative logics. Issue 1 (1st September 2021) - De Sordi, José Osvaldo; Nelson, Reed Elliot; Meireles, Manuel; Hashimoto, Marcos
Abstract : Purpose: The purpose of this paper is to make available an artifact that helps entrepreneurs and managers to recognize the diversity of creative logics centered on resources that are already available to the organization, presenting it as a tool to support the expansion of the product and service portfolio and as an alternative to Research and Development strategies, which are difficult to implement in the context of small businesses. Design/methodology/approach: Following the precepts of the Action Design Research (ADR) method, researchers and practitioners (teachers and consultants) collaborated in the development of the artifact. Successive versions of the artifact were tested in the field: in classrooms by the teachers and in small companies by the consultants. Findings: In addition to the artifact itself, which is available on the Internet, the lessons learned from the design process of the artifact were formalized in meta-requirements and meta-designs, in accordance with the precepts of the design theory that served as the foundation of ADR. These meta-specifications facilitate the critical analysis and evolution of the proposed artifact, in addition to the conception and proposition of new artifacts for the same class of problem. Practical implications: The dialogical nature of the ADR approach, with the development of the artifact through interactive cycles between design and use, based on the practitioners' experience of using it with the final beneficiaries, resulted in a functional artifact that is simple to use by those interested in discussing product and service innovation with small organizations. The artifact in the form of software is available to all at https://tentypescreation.com . Originality/value: From business examples and comparisons with widespread creative tactics, such as copy and invention, eight other creative tactics centered on resources available in the organization are explored by the artifact, providing means for practitioners to discuss alternative ways for managers, entrepreneurs, and future entrepreneurs to face the challenge of product and service innovation in small businesses.